Strategies for Managing Government Microblogs:A Critical Study of 29 Provincial Weibos in China - Hou, Runtian (Université d'Ottawa | University of Ottawa, 2016)
It is becoming widely believed that social network is posing an insurmountable threat to authoritarian rule, as the role tweeter played in the Arab Spring. However, Chinese government is benefiting from the proper use of Weibo (the Chinese name for microblog) instead of just regarding it as a danger. Chinese government is using Weibo to build a more responsive government and meanwhile avoiding the potential for collective movement. Although numerous scholars have studied astroturfing1 and censorship in weibo, there’s no systematic study of how both activities work in the government weibo. In this critical study, we found provincial governments use weibos for responding to the demand from various social actors and applying different strategies to manage comments in weibo. Furthermore, we found there’s a regional difference in the above strategies. Key words: weibo, astroturfing, censorship, tolerance, authoritarian resilience, responsive government